2017
DOI: 10.1115/1.4035282
|View full text |Cite
|
Sign up to set email alerts
|

On the Transient Three-Dimensional Tribodynamics of Internal Combustion Engine Top Compression Ring

Abstract: There are increasing pressures upon the automotive industry to reduce harmful emissions as well as meeting the key objective of enhanced fuel efficiency, while improving or retaining the engine output power. The losses in an internal combustion (IC) engine can be divided into thermal and parasitic as well as due to gas leakage because of untoward compression ring motions. Frictional losses are particularly of concern at low engine speeds, assuming a greater share of the overall losses. Piston–cylinder system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…In this study, the hydrodynamic pressure of oil film in CRCL considering the variable density and viscosity in the x, y, and z directions can be described by the generalized Reynolds equation. Moreover, the surface roughness affects greatly the lubrication performance of CRCL, especially under the mixed/boundary lubrication regime [9]. In order to simulate the effects of surface roughness on the lubrication performance, two different methods (i.e., the direct/deterministic method and the indirect/stochastic method) are usually adopted [32,33].…”
Section: Governing Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the hydrodynamic pressure of oil film in CRCL considering the variable density and viscosity in the x, y, and z directions can be described by the generalized Reynolds equation. Moreover, the surface roughness affects greatly the lubrication performance of CRCL, especially under the mixed/boundary lubrication regime [9]. In order to simulate the effects of surface roughness on the lubrication performance, two different methods (i.e., the direct/deterministic method and the indirect/stochastic method) are usually adopted [32,33].…”
Section: Governing Equationmentioning
confidence: 99%
“…For PRCL in working conditions, various regimes of lubrication (hydrodynamic, mixed, and boundary) will be encountered in an engine cycle because of the rapidly changing velocity, highly fluctuating thermal and structural loads [8]. Generally, the PRCL is under hydrodynamic regime in the majority of the engine cycle, and under mixed or boundary regimes at piston dead centers [9]. In consideration of the dominant lubrication regime of hydrodynamic in the engine cycle of PRCL, Jeng et al [10] conducted a one-dimensional lubrication analysis for PRCL by solving Reynolds equation.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the thin nature of the piston ring, analytical and experimental reports were also presented on ring tribology for different engine conditions. Numerical predictions and experimental measurements of the piston ring-liner mechanism were presented by Rahmani et al [17], Baker et al [18], and Zavos et al [19]. It was found that the elastodynamics thin ring performance showed thinner lubricant films and higher friction values when hot engine conditions were expected.…”
Section: Introductionmentioning
confidence: 99%
“…A disproportionate 5% of the total engine losses can be attributed to the piston compression ring [1], especially when considering its small size. The thinness of the ring constitutes high modal density, exciting a plethora of responses during the engine cycle, resulting in a number of undesired phenomena such as ring flutter, ring jump, twist, and rotation [2][3][4][5][6][7][8][9], as well as promoting blow-by [10].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, a tribological study of the conjunction provides important input for a ring dynamic analysis [4][5][6]16] such as the generated contact pressures, load carrying capacity, and friction. Furthermore, the ring's dynamic behavior determines important parameters within a gas flow analysis through the ring pack in an IC engine [2,3,7,8]. This is utilized for the prediction of the phenomena underlying gas blow-by, loss of sealing and power loss, as well as lubricant degradation.…”
Section: Introductionmentioning
confidence: 99%